Nordic experience of fisheries management. Seen in relation to the reform of the EU Common Fisheries Policy. - Eliasen, Søren; Holm, Petter; Sverdrup-Jensen, Sten; Johnsen, Jahn Petter (Norden - Nordic Council of Ministers, 2009)
The waters surrounding the Nordic countries are rich in fish resources. Up to this date fisheries has been among the most important productive sectors in the Nordic economies, and in the Faroe Islands and Greenland it is by far the most important sector. Management of marine fisheries has over time had various objectives in the Nordic countries, ranging from fiscal and social purposes to stock conservation and socio-economic well-being in recent years. There are strong similarities between the Nordic countries, but differences in ecosystem and the socio-cultural settings of the fisheries have lead to differentiated management systems anyhow. The purpose of this note is to bring Nordic experience into the discussion of the reform of the Common Fisheries Policy. The discussion takes as its point of departure the so-called Green Paper in which the Commission has summarised the status of the EU fisheries and also put themes and questions up for discussion. The themes and cases of this note address issues which feature prominently in the Green Paper: reduction of over-capacity by establishing rights-based management systems, increase of the responsibility of the industry through development of co-management arrangements, and reduction of the discard of fish.